The Differences of Students Achievement Between Those Who Take Course and Those Who do Not Take Course in Four Basic Skills of English - Sihite , Jubilezer (Pascasarjana Universitas HKBP Nommensen, 2021)
This an experimental research is a kind of comparative research that the population is all the students of the third semester to compare the score achievement of those students who takes or not taking the course in basic skill subjects Based on the result of the data analysis in this research, it can be seen that there is a significant difference in learning outcomes between the two groups, where the average of student achievement who take course is 38.48, while the average of students achievement who do not take the course is 30, 47. There is a significant difference in students’ achievement between those students who take course and who do not take course. The significant difference in learning outcomes is also proven by conducting hypothesis test by using t-test and confidence level α = 0.05, where tcount>ttable (0.60> 0.021) means that in this research Hois rejected and HA is accepted. Thus, it can be concluded that there is a significant difference in student achievement between those students who take course and those students